Control factors on the composition of superficial sediments in estuaries of the coast of Huelva (SW Spain): a statistical approach. - Borrego, J.; Carro, B.; Grande, J.A.; de la Torre, M.L.; Valente, T.; Santisteban, M. (Journal of Iberian Geology, 2013)
The geochemical composition of surface sediments has been analyzed for the following three river estuaries located in the Huelva coast (SW Spain): Guadiana, Piedras and Tinto-Odiel (Ría de Huelva), which represent an area strongly affected by mining activity, mainly for Cu exploitation in the Iberian Pyrite Belt. The main goal of the present study was to evaluate the water and sediment quality of the three estuary systems, which have been subject to different types of anthropogenic activity. Enrichment factors (EF) for several elements were determined for each system, using as reference the composition of the sediments from the Huelva Ría, prior to the intensive mining and industrial activity. Statistical treatment based on factorial analysis allowed establishing the origin of the elements and the main control factors of their geochemical behaviour in the estuarine systems. The estuary of Tinto-Odiel rivers (Ría de Huelva) presents high metal concentrations and strong EF for metals related to acid mine drainage, namely Cu (EF of 75,6), Zn (EF of 36,9), and Pb (EF of 58), indicating severe environmental quality problems. On the contrary, the sediments of the Guadiana and Piedras rivers show no significant EF. Here, the obtained results indicate the absence of antropic metallic contributions, which permits the maintenance of the environmental quality of both systems. Thus, the present study revealed the environmental quality problems of the sediments from Tinto-Odiel estuary, while in Guadiana and Piedras there are no significant metallic contributions, ensuring the maintenance of the their environmental quality.